ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS WITH ISCHEMIC DIABETIC FOOT SYNDROME AFTER ENDOVASCULAR TREATMENT - Puzyrov, G.S.; Liakhovskyi, V.I. (World of Medicine and Biology, 2023)
The clinical course of diabetic foot syndrome negatively affects the quality of life of patients. Assessment of quality of life will help ensure better care and treatment of patients with this pathology and reduce the likelihood of severe complications of diabetes mellitus. The purpose of the study was to evaluate the quality of life of patients with the ischemic form of diabetic foot syndrome after endovascular treatment by various methods. Patients with the ischemic form of diabetic foot syndrome, depending on the method of balloon angioplasty of occlusive-stenotic lesions of the popliteal and tibial arteries, were divided into two study groups. Patient’s quality of life was assessed using the SF-36 questionnaire before, 7–10 days, and 6 months after surgery. 38 (65.5 %) patients of the first and 34 (63.0 %) patients of the second group, who were included in this study, passed all stages of the survey within 6 months of observation. The obtained data make it possible to state that balloon angioplasty of the popliteal and tibial arteries in patients with the ischemic form of diabetic foot syndrome positively affects the patients’ subjective assessment of their physical and mental health state both immediately after such operations and 6 months after their implementation.